The Devil You Know: An Exploration of Virtual Religious Deconstruction Communities - Fekete, Steven (Journal of religion, media and digital culture, 2020)
In a 2018 episode of the podcast The Airing of Grief, musician Derek Webb spoke with a caller about the fact that social media, live performances/events, and podcasts have become some of the few community spaces where religious and formerly religious people are able to deconstruct their faith experiences and process their doubts and questions. This observation began a research project regarding the question of community formation around religious deconstruction/reconstruction and its specific relation to social media spaces. As this research revealed, these deconstruction communities are safe spaces in which participants feel and experience radically open, loving, and supportive community (something that was promised or sought in previous religious spaces but rarely was experienced). The public and broad connecting aspects of social media and podcasts have allowed those who previously experienced deconstruction or doubts in isolation to find support and connections.